Three tesla and 3D multiparametric combined imaging evaluation of axial spondyloarthritis and pelvic enthesopathy. Issue 126 (May 2020) - Chhabra, Avneesh; Ezzati, Fatemeh; Taurog, Joel D.; Xi, Yin; Pezeshk, Parham
Highlights: Axial spondyloarthritis (SpA) has challenging diagnosis due to temporal findings. We studied the diagnostic value of 3 T multiparametric combined MR imaging in SpA. 41 patients were enrolled to assess the detailed imaging and lab findings. MRI protocol was able to provide extensive findings helpful in SpA diagnosis. It provides a better insight to clinicians for diagnosis and monitoring of SpA. Abstract: Purpose: Axial spondyloarthritis (SpA) is a group of diseases with temporally disseminated symptoms and clinical signs, which render the diagnosis challenging. Laboratory and MRI findings are used in addition for confirming the diagnosis and evaluation of disease activity. The purpose of this study was to evaluate clinically suspected axial SpA to determine the technical success of a multiparametric and 3D rheumatology lumbosacral MR imaging (MRLI) protocol and to assess the disease distribution, inter-reader reliability, and impact on patient management. Methods: A consecutive series of patients with clinical suspicion of axial SpA were included. Two rheumatologists recorded the clinical findings and disease activity on a confidence scale before and after MRLI. Two musculoskeletal (MSK) radiologists read the imaging data including enthesitis, arthritis, osseous lesions, ADC values, and enhancement. Prevalence-adjusted and bias-adjusted kappa (PABAK), ICC and Fisher exact test were calculated. Results: There were 41 patients including 31 females and 10 males with ages of 41 ± 10 and 41 ± 12 (mean ± SD), respectively. The spine T2W imaging received the highest quality scores followed by whole abdomen-pelvis 3D-T2W imaging, 3D-CEMR (contrast-enhanced MRI), and DWI. On spine imaging, acute and chronic lesions of lumbar spine and sacroiliac joints were seen in 4/41, 18/41 and 6/41, and 27/41 of the patients, respectively. Several additional enthesopathy lesions were seen on the whole abdomen-pelvis 3D sequence. ADC value of bone lesions was different 0.95 ± 0.23 (mean ± SD) than normal bone (0.20 ± 0.1). PABAK for acute and chronic findings ranged 0.70–1.0 and 0.41-0.51, respectively. Imaging changed the diagnosis in 17 of 41 patients. No association was noted with respect to treatment change (p = 1) or clinical response (p = 0.2). Conclusion: Multiparametric lumbosacral MR imaging is a technically successful modality to identify multiple spinal and additional extraspinal sites of involvement in SpA, which are helpful in establishing the diagnosis of axial SpA. Larger patient population study is warranted to evaluate further impact on the treatment efficacy.